Fail More : Embrace, Learn, and Adapt to Failure As a Way to Success - Wooditch, Bill (McGraw-Hill's AccessEngineering., 2019)
The business professional's guide to building success out of failure Learning from our mistakes is the only way to make sure we don't make the same ones twice. But what if you could use every failure-large and small-to actually create a successful business, career, and life? You can. Fail More provides the knowledge, insight, and tools to do just that. This one-of-a-kind guide teaches you how to take active, strategic measures to turn the sting of failure into the reward of growth. It reveals the setbacks that are both inevitable and valuable, and it delivers practical ways of quickly moving past self-judgment and -recrimination to: u2022Create large and small goals u2022Establish milestones for achieving them u2022Analyze data to determine what worked and what didn't u2022Make the necessary corrections to your method u2022Determine what you need and adjust accordingly u2022Evaluate your actions u2022Assess your progress while refining your game plan u2022Use failing as a core tool for motivation By embracing failure, not just "getting past it," you will fly past your competition, whether you're building a startup, advancing in your career, or improving your personal life. "Learning from our mistakes is the only way to make sure we don't make the same ones twice. But what if you could use every failure--large and small--to actually create a successful business, career, and life? You can. Fail More provides the knowledge, insight, and tools to do just that. This one-of-a-kind guide teaches you how to take active, strategic measures to turn the sting of failure into the reward of growth."--Publisher's description.